DOI: 10.20868/upm.thesis.56492
|View full text |Cite
|
Sign up to set email alerts
|

A new concept in thermal engineering optimization : the pericritical cycle with multi-heating and its application to concentrating solar power

Abstract: 'Proceso cíclico termodinámico sin condensación del fluido con prescripciones acotadas sobre sus puntos de mínima y máxima entalpía y dispositivo para su realización', ES2652522B2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…where δ w mc /w t is the variation of the dimensionless main compression work of the sCO 2 -mixtures respect to the pure s-CO 2 , δ w rc /w t is the variation of the dimensionless recompression work of the sCO 2 -mixtures respect to the pure s-CO 2 , δ ∆h a /w t is the variation of the dimensionless additional enthalpy of the sCO 2 -mixtures respect to the pure s-CO 2 , and δ total is the total variation of the dimensionless cycle work of the sCO 2 -mixtures respect to the pure s-CO 2 . It has been observed that the cycle efficiency increases when δ total increases [40]. Therefore, the influence of the dimensionless variables w mc /w t , w rc /w t and ∆h a /w t on the cycle efficiency can be displayed in Figure 7.…”
Section: Results Of 'Group A' Mixtures (Substances For Reducing the Cmentioning
confidence: 95%
“…where δ w mc /w t is the variation of the dimensionless main compression work of the sCO 2 -mixtures respect to the pure s-CO 2 , δ w rc /w t is the variation of the dimensionless recompression work of the sCO 2 -mixtures respect to the pure s-CO 2 , δ ∆h a /w t is the variation of the dimensionless additional enthalpy of the sCO 2 -mixtures respect to the pure s-CO 2 , and δ total is the total variation of the dimensionless cycle work of the sCO 2 -mixtures respect to the pure s-CO 2 . It has been observed that the cycle efficiency increases when δ total increases [40]. Therefore, the influence of the dimensionless variables w mc /w t , w rc /w t and ∆h a /w t on the cycle efficiency can be displayed in Figure 7.…”
Section: Results Of 'Group A' Mixtures (Substances For Reducing the Cmentioning
confidence: 95%
“…S-CO 2 inlet and outlet temperatures are determined by the power cycle configuration and particle inlet and outlet temperatures are inputs in the EES code. For the calculation of the conductance, the heat exchanger is discretized into N HX sub-heat exchangers with the same heat duty , and the sum of sub-heat exchanger conductances UA i is the total conductance, UA [ 29 ]: where is the logarithmic mean temperature difference.…”
Section: Modelmentioning
confidence: 99%
“…This line separates liquid and gas behaviors both below and above the critical pressure. The discontinuity line is defined as the line that consists of points with maximum value of fP for each pressure, where fP is defined in Equation 3.1 [16,31].…”
Section: Best Conditions For Multi-heating Cyclesmentioning
confidence: 99%